Kupilikula: Governance and the Invisible Realm in Mozambique - West, Harry G. (University of Chicago Press, 2005)
On the Mueda plateau in northern Mozambique, sorcerers are said to feed on their victims, sometimes "making" lions or transforming into lions to literally devour their flesh. When the ruling FRELIMO party subscribed to socialism, it condemned sorcery beliefs and counter-sorcery practices as false consciousness, but since undertaking neoliberal reform, the party—still in power after three electoral cycles—has "tolerated tradition," leaving villagers to interpret and engage with events in the idiom of sorcery. Now, when the lions prowl plateau villages ,suspected sorcerers are often lynched. In this historical ethnography of sorcery, Harry G. West draws on a decade of fieldwork and combines the perspectives of anthropology and political science to reveal how Muedans expect responsible authorities to monitor the invisible realm of sorcery and to overturn or, as Muedans call it, "kupilikula" sorcerers’ destructive attacks by practicing a constructive form of counter-sorcery themselves. Kupilikula argues that, where neoliberal policies have fostered social division rather than security and prosperity, Muedans have, in fact, used sorcery discourse to assess and sometimes overturn reforms, advancing alternative visions of a world transformed.
free